TRANSFORMASI PARADIGMA KEMESIASAN YESUS SEBAGAI MODEL PERAN PANUTAN BAGI PENDIDIKAN POLITIK KRISTEN : SEBUAH PANDANGAN TEOLOGIS BERDASARKAN DANIEL 7:13-14 & MARKUS 8:27-30 - Desy Flourensia Balo; Yohan Brek (PT. GIAT KONSELING NUSANTARA, 2024)
The transformation of the Messianic paradigm of Jesus as a role model for Christian political education addresses and actively participates in Indonesian democracy in the context of the 2024 elections. In this political situation in Indonesia, Jesus is seen as a figure who exemplifies how to interact with the world of politics in an ethical and integrity manner. Based on the theological view from Daniel 7:13-14 regarding the Son of Man, Jesus' Messiahship is emphasized again in Mark 8:27-30. Dismissing the Jewish view represented by Peter regarding Jesus as the Revolutionary Messiah, Jesus actually exemplifies a very different paradigm. He is not a political leader but his leadership values ​​are visible in his service which aims for a new, more dignified way of life. This paradigm suggests that Christian political education should focus on teaching values ​​such as justice, compassion, and service to others, in line with the teachings of Jesus. This transformation is important in the current political context, where integrity and ethics are often questioned. By taking Jesus as a role model, Christian political education can help form leaders with principles and integrity.